2018
DOI: 10.3390/hydrology5020023
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Impact Evaluation for Near Real-Time Flood Detection in the Lower Mekong River Basin

Abstract: Flood events pose a severe threat to communities in the Lower Mekong River Basin. The combination of population growth, urbanization, and economic development exacerbate the impacts of these events. Flood damage assessments, critical for understanding the effects of flooding on the local population and informing decision-makers about future risks, are frequently used to quantify the economic losses due to storms. Remote sensing systems provide a valuable tool for monitoring flood conditions and assessing their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It is important to note that the final goal of this work was not to estimate floods and extreme events, but to evaluate the performance of satellite precipitation estimates so that future studies can feel confident about using these estimates in their models. This study and further research applying in-situ observations to determine accuracy of satellite product can aid in the improvement of basin-wide decision-making, flood prediction, and management of floodwaters and drought by providing validations which suggest that satellite estimates can substitute for rain gauge measurements in areas with a sparse or absent in-situ network [26,33].…”
Section: Introductionmentioning
confidence: 88%
“…It is important to note that the final goal of this work was not to estimate floods and extreme events, but to evaluate the performance of satellite precipitation estimates so that future studies can feel confident about using these estimates in their models. This study and further research applying in-situ observations to determine accuracy of satellite product can aid in the improvement of basin-wide decision-making, flood prediction, and management of floodwaters and drought by providing validations which suggest that satellite estimates can substitute for rain gauge measurements in areas with a sparse or absent in-situ network [26,33].…”
Section: Introductionmentioning
confidence: 88%
“…produced automatic flood extents by applying a dynamic surface water classifier to data from the Moderate-resolution Imaging Spectroradiometer (MODIS) sensors on the Aqua and Terra satellites. Oddo et al (2018) then demonstrated how the resulting flood extents can be combined with socioeconomic data to produce rapid estimates of flood impacts using depth-damage curves for different types of land cover and infrastructure. This study attempts to determine how the flood detection and impact assessment metrics produced by the preceding analyses can be further applied to emergency response (Figure 3).…”
Section: The Value Of Applied Earth Observations In Emergency Managementmentioning
confidence: 99%
“…Subtracting the underlying digital elevation model ("Multi-Error-Removed Improved-Terrain"-MERIT DEM) produces a raster of estimated flood depths (Figure 1c) (Yamazaki et al, 2017). For a more detailed discussion of the methodology and limitations of this approach, see sections 3 and 5 of Oddo et al (2018).…”
Section: Flood Impact Assessment: 2011 Southeast Asia Floodsmentioning
confidence: 99%
See 2 more Smart Citations